CABARAN PENGUATKUASAAN UNDANG-UNDANG BAGI KESALAHAN JENAYAH SYARIAH MENGAJAR AGAMA TANPA TAULIAH DI ALAM SIBER: KAJIAN DI BAHAGIAN PENGUATKUASAAN UNDANG-UNDANG JABATAN AGAMA ISLAM WILAYAH PERSEKUTUAN : Challenges in Enforcement of Shariah Criminal Offence Relating to Offence of Teaching Islam without Credentials in Cyberspace: A Study in Law Enforcement Division Department of Federal Territory Islamic Affairs - Ibrahim, Nurulain; Samudin, Siti Aisyah (Journal of Shariah Law Research, 2022)
This article focused on the challenges in enforcing the shariah criminal offences related to offence in teaching Islam without credentials in cyberspace. This research also focused on the challenges faced by the Islamic Enforcement Officer at Law Enforcement Division, Department of Federal Territory Islamic Affairs. This research will explain regarding the relevance of the offence of teaching Islam without credentials committed in cyberspace alleged pursuant to provision of Section 11 of Syariah Criminal Offences Act Federal Territory 1997. In identifying the challenges enforcing these offences, researcher will explain regarding the background of the relevant authority in enforcing these offences. After the relevant authority is identified, the challenges in enforcement the offence will be elaborated. Data were obtained from research of several books and interview, and the data were analyzed using inductive and deductive methods. The results found that Section 11 of the Syariah Criminal Offences (Federal Territories) Act 1997 is less comprehensive to prosecute the offence of teaching Islam without credentials committed in cyberspace. In fact, various challenges do exist in enforcing these offences. Therefore, there is a need for the existing law to be improvised to cater all types of challenges, in order to enable these offences to be fully enforced either physically or in cyberspace.